2014 8th Asia Modelling Symposium 2014
DOI: 10.1109/ams.2014.43
|View full text |Cite
|
Sign up to set email alerts
|

Air Pollution and Fog Detection through Vehicular Sensors

Abstract: Abstract-We describe a method for the automatic recognition of air pollution and fog from a vehicle. Our system consists of sensors to acquire main data from cameras as well as from Light Detection and Recognition (LIDAR) instruments. We discuss how this data can be collected, analyzed and merged to determine the degree of air pollution or fog. S uch data is essentaial for control systems of moving vehicles in making autonomous decisions for avoidance. Backend systems need such data for forecasting and stragte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…The number of points N t ( f 1,2,3 ) and mean distances r t are derived for each echo t ∈ 1, 2, 3 for the first, second or last return separately. The eigenvalues ( f13,14,16 ) were calculated from the covariance matrix of all points.…”
mentioning
confidence: 99%
“…The number of points N t ( f 1,2,3 ) and mean distances r t are derived for each echo t ∈ 1, 2, 3 for the first, second or last return separately. The eigenvalues ( f13,14,16 ) were calculated from the covariance matrix of all points.…”
mentioning
confidence: 99%
“…In the case of camera sensors, the idea will be focused on the approach of enhancing visibility [25,26]. In the case of laser sensors, the analysis will be based on the surface patterns characteristic of the road in the presence of rain water [27] or fog [28]. Research in [7] showed that, in the case of nighttime, the laser demonstrates good performance.…”
Section: Methodsmentioning
confidence: 99%
“…However, examining Fig. 6 one can observe that relative to fog, in rain there is much higher attenuation [45], [46]. In an explicit study of the effects of adverse weather on automotive radar, Zhang et al [47] note that rain, snow, mist, and hail, can all have a significant impact, showing for example how the received power and probabilities of detection of vehicles and pedestrians reduce considerably as rain density increases.…”
Section: A Comparison With Automotive Radarmentioning
confidence: 99%
“…If fog (or other weather) is an impediment to optical imaging because it attenuates and degrades the recorded image, the corollary is that measurements of passive optical and LiDAR image data can be used to estimate fog or other pollutant densities [45]. Pfennigbauer et al [22] suggested that it was possible to determine the visibility range and hence estimate fog density from a LiDAR waveform measured from immediately in front of the sensor to a maximum range of 30 m, since the rate of amplitude decay was a clear indication of this.…”
Section: E Online Fog Determinationmentioning
confidence: 99%